The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Inflammatory Diseases - Immunopathology, Clinical and Pharmacological Bases 2012
DOI: 10.5772/25563
|View full text |Cite
|
Sign up to set email alerts
|

Polymerized Type I Collagen Reverts Airway Hyperresponsiveness and Fibrosis in a Guinea Pig Asthma Model

Abstract: Asthma is a chronic, heterogeneous and variable disease in which airways inflammation, transient obstruction and hyperresponsiveness are the major features of the illness (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Group II exhibited less lymphocytic infiltrate possibly because the compound reduces chemotaxis and lymphocyte stimulation in chronic inflammatory processes [6], which corroborates the findings of tracheal surgery studies [10, 23] and studies performed in guinea pigs with asthma treated with Collagen-PVP, which showed low numbers of lymphocytes during tissue remodeling [25]. Our findings also corroborate those by Furuzawa-Carballeda et al [26], who assessed the safety of Collagen-PVP in vitro and in vivo and noted that this biopharmaceutical does not stimulate lymphocyte proliferation.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Group II exhibited less lymphocytic infiltrate possibly because the compound reduces chemotaxis and lymphocyte stimulation in chronic inflammatory processes [6], which corroborates the findings of tracheal surgery studies [10, 23] and studies performed in guinea pigs with asthma treated with Collagen-PVP, which showed low numbers of lymphocytes during tissue remodeling [25]. Our findings also corroborate those by Furuzawa-Carballeda et al [26], who assessed the safety of Collagen-PVP in vitro and in vivo and noted that this biopharmaceutical does not stimulate lymphocyte proliferation.…”
Section: Discussionsupporting
confidence: 66%
“…Animals in groups I and III developed more severe histological inflammation because the treatments applied in these groups do not exhibit anti-inflammatory activity, and our findings corroborate other studies of the use of MMC for the treatment of TS that reported that this drug causes lesion site irritation up to two months after its application, which favors inflammation [ 8 , 20 ]. Conversely, animals treated with Collagen-PVP developed mild-to-moderate inflammation because this drug exhibits anti-inflammatory properties over short and long periods of administration, as previously observed in clinical and experimental studies of patients with rheumatoid arthritis, hypertrophic skin scars, scleroderma, bedsores, and posttracheoplasty scars [ 10 , 25 , 26 ]. The animals treated with PFD showed no-to-mild inflammation because its oxidative stress-preventive properties inhibited the recruitment of proinflammatory cells [ 11 ], as observed in the present study and reported by studies of the effects of PFD on experimental models of pulmonary fibrosis [ 16 , 27 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Direct stimulation of ASM with agonists such as histamine or indirect provocation with antigens in guinea pigs produce robust airway obstruction because guinea pigs have a large ASM mass [ 17 ]. In addition to the extrinsic responses induced by direct and indirect provocation, the guinea pig asthma model has shown an increase in intrinsic baseline tone [ 18 ].…”
Section: Introductionmentioning
confidence: 99%